COMMON DEFICIENCIES RAISED BY VARIOUS REGULATORY AGENCIES - Mohidekar, S.; Maharao, V.; Badjatya, J. K. (International Journal of Drug Regulatory Affairs, 2018)
Timely Product registration is a challenge in today’s scenario. Regulatory agencies are keen in assessing CTD sections like redefining starting material of Drug substance manufacturing, Pharmaceutical development, impurities in Drug substance and Drug product, Container-closure. Common deficiencies are presented in this article.